Edukasi Pentingnya Pembukuan Bagi Pelaku Umkm Cireng Aisyah di Pekanbaru - Rahma Maulida Erizal; Annisa Safitra; Putri Fauzely Mulia; Rafly Armazumi; Richard Ginting; Muhammad Richard Ginting; Siti Rodiah (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Small and medium enterprises (MSMEs) have an important role in the Indonesian economy. Based on a Bank Indonesia report, MSMEs account for 99.99% of the total number of business entities in Indonesia or 56.54 million units. MSME players, especially those with creative economy products, are able to contribute to gross domestic product (GDP) of IDR 852 trillion and absorb a workforce of 15 million people. This approach is used to describe and analyze the importance of bookkeeping for BCireng Aisyah MSMEs in Pekanbaru in depth through interviews, observations and document analysis. The aim of the research is to increase understanding and awareness of MSME players, especially Cireng Aisyah in Pekanbaru, about the importance of good and correct bookkeeping. Quite a lot of Pekanbaru people work as entrepreneurs, especially in the economic sector of micro, small and medium enterprises (MSMEs), such as processed food producers.